2008
DOI: 10.1021/jp807273v
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Molecular Rotational Dynamics at a Negatively Charged Surfactant/Aqueous Interface

Abstract: The in-plane rotational dynamics of the molecular probe coumarin 314 (C314) at the negatively charged surfactant sodium dodecyl sulfate (SDS)/aqueous interface was measured using femtosecond time-resolved second-harmonic spectroscopy. The in-plane orientational time constant at an SDS surface coverage of 100 Å 2 per SDS molecule is 348 ( 12 ps, which is comparable to the out-of-plane reorientational time of 383 ( 9 ps at the same SDS density. At 100 Å 2 , the SDS surfactant forms a homogeneous monolayer becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 51 publications
0
28
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Time-resolved SHG has also been used to study solvation dynamics, rotational dynamics, electron transfer, population recovery, two-dimensional energy transfer, and other ultra-fast processes. [25][26][27][28][29][30] SFG is a powerful method to investigate structural dynamics, vibrational energy relaxation, thermal transport, and other interfacial processes. 19,[31][32][33][34][35][36][37] In recent work, we have used visible-pump-time-resolved vibrational SFG experiments to study rotational dynamics of a single chemical group of a molecule at the air/water interface using the visible-pump-SFG probe technique.…”
Section: The Journal Of Chemical Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Time-resolved SHG has also been used to study solvation dynamics, rotational dynamics, electron transfer, population recovery, two-dimensional energy transfer, and other ultra-fast processes. [25][26][27][28][29][30] SFG is a powerful method to investigate structural dynamics, vibrational energy relaxation, thermal transport, and other interfacial processes. 19,[31][32][33][34][35][36][37] In recent work, we have used visible-pump-time-resolved vibrational SFG experiments to study rotational dynamics of a single chemical group of a molecule at the air/water interface using the visible-pump-SFG probe technique.…”
Section: The Journal Of Chemical Physicsmentioning
confidence: 99%
“…Time-resolved polarized SFG experiments used a pump pulse to photoselect an orientational subset of the equilibrium distribution of ground state molecules, which thereby generate a non-equilibrium orientational distribution in both the ground state molecules that were not excited and the excited state molecules produced by the pump pulse. 27,28,30,32,39,40 Depending on the polarization of the pump pulse, the change in the SFG intensity with time can depend on both in-plane and out-of-plane rotations. It has been shown that the out-of-plane rotations can be separated from the in-plane rotations by using a circularly polarized laser pump pulse that is incident normal to the interfacial plane.…”
Section: The Journal Of Chemical Physicsmentioning
confidence: 99%
“…[219][220][221] In contrast, time-resolved studies at liquid interfaces are much more difficult to do, so they have been limited to several timeresolved SHG and SFG measurements addressing the reorientation dynamics of dye molecules at the water liquid/vapor interface. 223,[469][470][471][472][473][474][475] A few theoretical studies using molecular dynamics simulations have appeared. 228,[476][477][478][479] They were motivated by some conflicting reports about the ability of the interface region to enhance The reduced density at a liquid/vapor interface is expected to lower the collision frequency and to reduce the rate of rotational energy relaxation.…”
Section: Solute Rotational Relaxation At Liquid Interfacesmentioning
confidence: 99%
“…The in-plane rotational dynamics of C314 at the surfactant sodium dodecyl sulfate (SDS)/aqueous interface have been studied using femtosecond time-resolved second-harmonic spectroscopy. [12] In order to improve the solubility and chemical stability of molecules, inclusion complexes are nowadays largely used in the pharmaceutical field or whenever modulated properties of the guest are needed. Much interest has been shown on cyclodextrins (CDs), because of their remarkable ability to form host-guest inclusion complexes with a wide variety of molecules.…”
Section: Introductionmentioning
confidence: 99%